HS1 Is Involved in Hygromycin Resistance Through Facilitating Hygromycin Phosphotransferase Transportation From Cytosol to Chloroplast - Luo, Yanzhong; Zhang, Lan; Li, Weiwei; Xu, Miaoyun; Zhang, Chunyi; Wang, Lei (Frontiers in Plant Science, 2020)
The transportation of proteins encoded by nuclear genes from plant cytosol to chloroplast is essential for chloroplast functions. Proteins that have a chloroplast transit peptide (cTP) are imported into chloroplasts via translocases on the outer and inner chloroplast envelope. How proteins lacking transit sequence are imported into chloroplast remains largely unknown. During screening of an Arabidopsis population transformed with a hairpin RNA gene-silencing library, we identified some transgenic plants that had active expression of the selectable marker gene, hygromycin phosphotransferase (HPT), but were sensitive to the selection agent, hygromycin B (HyB). Mutant and complementation analysis showed that this HyB sensitivity of transgenic plants was due to silencing of the HS1 (Hygromycin-Sensitive 1) gene. HS1 is localized in the chloroplast and interacts physically with HPT in yeast cells and in planta. Fluorescence and immunoblotting analysis showed that HPT could not be transported effectively into chloroplasts in Aths1, which resulted in Aths1is sensitivity to hygromycin on higher HyB- containing medium. These data revealed that HS1 is involved in hygromycin B resistance in transgenic Arabidopsis through facilitating cytosol-chloroplast transportation of HPT. Our findings provide novel insights on transportation of chloroplast cTP-less proteins.